2000
DOI: 10.1348/000712600161718
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐typicality and attractiveness: Are supermale and superfemale faces super‐attractive?

Abstract: Many animals find extreme versions of secondary sexual characteristics attractive, and such preferences can enhance reproductive success (Andersson, 1994). We hypothesized, therefore, that extreme versions of sex-typical traits may be attractive in human faces. We created supermale and superfemale faces by exaggerating all spatial differences between an average male and an average female face. In Expt 1 the male average was preferred to a supermale (50% exaggeration of differences from the female average). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
173
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 29 publications
(46 reference statements)
14
173
2
Order By: Relevance
“…clearly above zero. This is in line with findings from previous studies that have reported a general preference for masculinity/masculine traits (Cunningham et al 1990;Gillen 1981;Grammer and Thornhill 1994;Koehler et al 2004;Neave et al 2003;Rhodes et al 2003Rhodes et al , 2007Saxton et al 2009;Scheib et al 1999), but in contrast to other studies which reported that overall, women prefer a close to average or slightly feminine male face shape (Little et al 2001;Penton-Voak et al 2004, 2003Perrett et al 1998;Rhodes et al 2000;Scott et al 2010). Our results might differ from these latter findings because we used an asymmetric range of masculinity (−100% to +200%).…”
Section: Resultssupporting
confidence: 89%
“…clearly above zero. This is in line with findings from previous studies that have reported a general preference for masculinity/masculine traits (Cunningham et al 1990;Gillen 1981;Grammer and Thornhill 1994;Koehler et al 2004;Neave et al 2003;Rhodes et al 2003Rhodes et al , 2007Saxton et al 2009;Scheib et al 1999), but in contrast to other studies which reported that overall, women prefer a close to average or slightly feminine male face shape (Little et al 2001;Penton-Voak et al 2004, 2003Perrett et al 1998;Rhodes et al 2000;Scott et al 2010). Our results might differ from these latter findings because we used an asymmetric range of masculinity (−100% to +200%).…”
Section: Resultssupporting
confidence: 89%
“…This explanation has been widely adopted within facial attraction research (e.g. Thornhill & Gangestad, 1999;Rhodes et al, 2000;Penton-Voak et al, 1999;Johnston et al, 2001). …”
Section: Immunocompetencementioning
confidence: 99%
“…Research has shown varying preferences for masculinity in male faces, with some studies finding a female preference for feminine looking males (e.g. Perrett, Lee, Rowland, Yoshikawa, Burt, Henzi, Castle & Akamatsu, 1998;Rhodes, Hickford & Jeffery, 2000) and some a preference for masculine looking males (e.g. Johnston, Hagel, Franklin, Fink, & Grammer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between attractiveness and male facial masculinity is not clear cut; some findings show attraction to masculinity (Cunningham et al 1990;DeBruine et al 2006;Grammer & Thornhill 1994) and others show attraction to femininity (Berry & McArthur 1985;Cunningham et al 1990;Little & Hancock 2002;Perrett et al 1998;Rhodes et al 2000).…”
Section: Introductionmentioning
confidence: 99%